A Comprehensive Review on Techniques and Challenges of Energy Harvesting from Distributed Renewable Energy Sources for Wireless Sensor Networks - Hussain, Md. Naeem; Halim, Md Abdul; Khan, Md. Yakub Ali; Ibrahim, Salah; Haque, Abrarul (Peneliti Teknologi Teknik Indonesia, 2024)
Wireless Sensor Networks (WSNs) have drawn a lot of interest from a variety of industries, such as industrial automation, healthcare, and environmental monitoring. Typically, these networks are made up of sensor nodes that run on batteries and depend on energy-efficient operation to extend their lifetime. Renewable and sustainable energies are suitable for wireless sensor networks. Energy harvesting from dispersed renewable sources, such as solar, wind, biomass, and vibration, has emerged as a possible approach to alleviate the limits associated with limited battery life. The state-of-the-art methods and difficulties associated with energy harvesting in wireless sensor networks (WSNs) from a variety of distributed renewable sources, such as solar, wind, vibration, and temperature gradients, are thoroughly reviewed in this study. The paper discusses the many techniques for extracting and converting energy from these sources, highlighting the benefits and drawbacks of each. This paper explores several energy harvesting techniques and challenges. The study also discusses the difficulties in integrating energy harvesting, including adaptive power management, energy forecast, intermittent energy supply, and integration issues. The assessment also highlights research gaps and potential future initiatives in the field of energy harvesting from renewable sources. Researchers, technologists, and policymakers working in the fields of renewable energy and wireless sensor networks would find this thorough assessment to be quite insightful. It illuminates how energy harvesting technologies may improve sensor network autonomy and sustainability, leading to breakthroughs in environmental monitoring and other vital applications. The development of sustainable, independent, and effective sensing systems is greatly aided by the investigation of methods and obstacles in energy harvesting for wireless sensor networks. In addition to addressing current issues, this research opens doors for innovation, fostering a more sustainable approach to data collection and monitoring, and having a positive effect on a number of industries.